2008
DOI: 10.1074/jbc.m707535200
|View full text |Cite
|
Sign up to set email alerts
|

Interdomain Interaction Reconstitutes the Functionality of PknA, a Eukaryotic Type Ser/Thr Kinase from Mycobacterium tuberculosis

Abstract: Eukaryotic type Ser/Thr protein kinases have recently been shown to regulate a variety of cellular functions in bacteria. PknA, a transmembrane Ser/Thr protein kinase from Mycobacterium tuberculosis, when constitutively expressed in Escherichia coli resulted in cell elongation and therefore has been thought to be regulating morphological changes associated with cell division. Bioinformatic analysis revealed that PknA has N-terminal catalytic, juxtamembrane, transmembrane, and C-terminal extracellular domains, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 43 publications
5
25
1
Order By: Relevance
“…These results suggest that the amino acids immediately flanking Thr 705 are required for the residue to function. This is consistent with previous reports that the flanking sequence is required for kinase autophosphorylation (41,42).…”
Section: Discussionsupporting
confidence: 83%
“…These results suggest that the amino acids immediately flanking Thr 705 are required for the residue to function. This is consistent with previous reports that the flanking sequence is required for kinase autophosphorylation (41,42).…”
Section: Discussionsupporting
confidence: 83%
“…D, trans-phosphorylation activity of KD and full-length ICD constructs was compared using GarA as a substrate. The autoradiogram confirms that the PknA ICD is more active than the PknA KD as reported previously (38), but that activity does not differ for the two PknB and PknL constructs. External mass calibration was performed prior to analysis using the standard LTQ calibration mixture.…”
Section: Methodssupporting
confidence: 74%
“…It must be stressed that other factors, such as molecular scaffolding and co-expression, may influence the cross-phosphorylation patterns in vivo. Moreover, the constructs used for in vitro biochemistry lacked possible regulatory sites in the juxtamembrane segments (24,38), potentially masking additional functional relationships. In addition, the network architecture may be modified by the temporally restricted activity of the STPKs mediated, in part by localization or regulation of the antagonistic phosphatase (50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6A). In vitro kinase assays have shown that the intracellular region consisting of the kinase and juxtamembrane domains is catalytically active (42). To delineate the domains of PknA required for cell survival in mycobacteria, we generated deletion mutants PknA KD (aa 1-271), PknA JM (aa 1-341), and PknA TM (aa 1-361) in pNit and pCiT vectors (Fig.…”
Section: The Extracellular Domain Of Pkna Is Dispensable For Cellmentioning
confidence: 99%